(untitled) (Gestión y Gerencia, 2022)
The Dean of Economic and Business Sciences (DCEE) of Universidad Centroccidental Lisandro Alvarado, in its beginnings School of Administration, is part of the institutions with which Universidad Centroccidental Lisandro Alvarado was established between 1962 and 1967. In this sense, the objective of this essay, of a theoretical nature -descriptive, is to offer a review of its evolution throughout its fifty-five years. The work was carried out based on various institutional documents and reports, both from Universidad Centroccidental Lisandro Alvarado and DCEE, and scientific articles related to the subject in order to consider the perspective of the consulted authors. As a reflection, it can be affirmed that the DCEE continues to open doors, contributing to the achievement of institutional commitment and the values that have allowed Universidad Centroccidental Lisandro Alvarado to continue building the future in these 60 years.